Competencias digitales de los jóvenes en el momento de entrada en la universidad - José Lagarto; Antonio Chenoll (Universidade Católica Portuguesa, 2021)
The teachers' perceptions of the students who reach the first year of the University are that they, sometimes so-called digital natives, do not have digital maturity that allows them to face not only the academic obstacles, but also the future challenges of working life. To detect the difficulties of developing competencies and the application of strategies for solving problems involving technology should be considered a fundamental and priority element for optimizing the formal learning process. In this way, it is necessary to know the contrast between what students think they know and what they really can do. In this study, we tried to identify what students think about their own digital knowledge and performance profile and what the main tools they use. We found, through the analysis of results of two questionnaires that, in their perception they can solve their digital problems, but they recognize their low level of competence. However, issues of solving digital problems are identified by choosing inappropriate solutions. It is now up to the University, in the light of the results obtained, to create programs that will increase the digital skills of young students so that they can face a full, competitive, and digitally inclusive citizenship.